The Relationship between Personal Traits, Travel Motivation, Perceived Value and Behavioural Intention of Tourists Participating in Adventure Activities - Cavusoglu, Fatih; Avcıkurt, Cevdet (International Journal of Contemporary Economics and Administrative Sciences, 2021)
The personality traits of tourists and their instinct to travel are seen as factors influencing their holiday purchase decisions. In addition, it is known that the attractiveness characteristics of destinations are factors affecting tourists before or during the holiday purchase decision. At this point, knowing the personality traits of tourists, the factors push them to travel, and the factors pull them to a certain destination are very important for destination management organizations and managers of tourism and adventure activity businesses that aim to attract tourists to their destinations or businesses. In the scope of the research, an application has been carried out for tourists participating in adventure activities in Fethiye. Data were obtained from 405 tourists using the survey technique. As a result of the analysis, it was determined that there is a significant relationship between the personality traits and perceived value. In addition, it was found that there is a strong and significant relationship between the perceived value of tourists and their loyalty. Significant relationships were found between the perceived value of tourists and the factors pushing them to travel and pulling them to the destination. It has been found that there are significant relationships between the level of loyalty of tourists and the factors pushing them to travel and pulling them to the destination.